Rational fabrication of a two-photon responsive metal–organic framework for enhanced photodynamic therapy. Issue 24 (25th October 2021) - Yao, Xin; Pei, Xinxin; Li, Bo; Lv, Mengqi; Zhang, Wen; Ni, Bo; Zhang, Qiong; Tian, Yupeng; Xu, Changzhi; Li, Dandan
Abstract : ZnL1@MOF-199@FA can respond to the microenvironment of cancer cells, realizing chemodynamic therapy (CDT) and enhanced two-photon-induced photodynamic therapy (PDT). Abstract : The rational design of a specific platform that can address the unavoidable side effects of traditional cancer treatments is of great interest. In this sense, herein, an intelligent nanoplatform (ZnL1@MOF-199@FA ) with efficient reactive oxygen species (ROS) production ability in vitro with or without laser irradiation has been designed and fabricated. Furthermore, the loading of a two-photon active photosensitizer ZnL1 could induce 1 O2 and O2 ˙ − upon near-infrared light irradiation, showing a promising photodynamic therapy (PDT) outcome. Notably, in an acidic environment, the copper ions resulting from the degradation of MOF-199 could convert H2 O2 into O2 and ˙OH. Hereinto, the resulting O2 may mitigate the hypoxic environment and further promote PDT efficiency. This work provides a controllable strategy to construct functional materials with an enhanced PDT outcome in a hypoxic microenvironment.